Motivasi Kerja, Kepuasan Kerja dan Kinerja - Arni Surwanti (Jurnal Bisnis: Teori dan Implementasi, 2011)
The findings of several studies relating to motivation, job satisfaction and performance, the results of research that show motivation, satisfaction and performance possible is highly dependent on certain conditions, such as differences in personal needs, values, attitudes, interests and ability his task